Pemberdayaan Guru Bahasa Bali Jenjang SMA/SMK dalam Kebijakan Pemerintah Provinsi Bali - I Wayan Gede Wisnu; Ida Ayu Putu Purnami; Ni Putu Diana Sari (Kelola: Jurnal Manajemen Pendidikan, 2023)
This study describes the policies of the Provincial Government of Bali regarding the empowerment of Balinese language teachers. This departs from the district or city government's policy on empowering Balinese language teachers by appointing local government contract teachers who only reach the elementary and secondary education levels, as explored through previous research in Denpasar. Meanwhile, the SMA/SMK education level is under the authority of the Provincial Government (Bali), which will become the locus and focus of this research as follow-up research. Concerning this background, this research aims to describe (1) the implementation and (2) the policy implications of the Provincial Government of Bali in empowering Balinese language teachers. This research is designed as policy research using qualitative descriptive construction. In this case, the research data is conceived as an ideological substance and structure as an empirical actualization of Denpasar City Government policies obtained through documentation studies, interviews, and questionnaires. Research data analysis was carried out through reduction, classification, and interpretation. The results of this study indicate that (1) the implementation of the Bali Provincial Government's policy regarding the empowerment of Balinese language teachers in the form of delegation, arrangement, and mapping of Balinese language teachers Meanwhile, (2) the implications of the Bali Provincial Government policy regarding the empowerment of Balinese language teachers are in the form of balancing, strengthening, and developing Balinese language teachers.